Avaliação clínica do uso de pinos de fibra de carbono na restauração de dentes tratados endodonticamente : um estudo retrospectivo - Coppo, Priscilla Pessin (2010)
Clinical studies of devitalized teeth restored with posts show similar outcomes with regard to the percentage of faults or failures, despite many technical variations, methodological and operative between them. The failures are greater when dealing with teeth coronally destroyed or periapically compromised. The aim of this study was identify the effect of clinical variants that influence the longevity of treatment and prevalence of dislodgment of post, marginal caries, root fracture and periapical lesions was performed a retrospective analysis of clinical performance of teeth restored with carbon fiber post. 139 teeth were evaluated in 75 patients, three years after the date of cementing the posts. The teeth were root canal treatments, including preparations of the conduits to posts, and restorative treatments, performed by the same endodontist and prosthetics, respectively, according to standardized protocols. Through clinical, radiographic, photographic, endodontic reports and information obtained from medical records, the teeth were classified according to: tooth groups, type of endodontic treatment received, time span between the last endodontic session and bonded post, morphology of the post, amount of remaining dentin after crown preparation and prosthetic crown system used. There were no dislodgment of post, root fractures, or caries, and the rank was favorably for 99.3% (138 teeth) of endodontic treatment. According to these parameters, the outcomes of this study revealed that the clinical variations identified, that are considered unfavourable, were not determining for the failure, starting from the set of procedures and materials used for dental treatment of these patients.